Patterns of regional cortical dysmorphology distinguishing schizophrenia and chronic alcoholism - Sullivan, Edith V.; Mathalon, Daniel H.; Lim, Kelvin O.; Marsh, Laura; Pfefferbaum, Adolf (Biological psychiatry (1969), 1998)
This study used magnetic resonance imaging (MRI) to compare the extent and pattern of tissue volume deficit and cerebrospinal fluid volume enlargement in chronic alcoholics and schizophrenics. The subjects included 62 detoxified chronic alcoholics (26–63 years), 71 schizophrenics (23–63 years), and 73 controls spanning the adult age range (21–70 years). MRI volumes were adjusted for normal variation in head size and age established from the control group. Both patient groups showed widespread cortical gray matter volume deficits compared with controls, but only the alcoholics had white matter volume deficits. The schizophrenics had significantly greater volume deficits in the prefrontal and anterior superior temporal gray matter than in the more posterior cortical regions. By contrast, the deficits in the alcoholics were relatively homogeneous across the cortex. For white matter, the deficits in the alcoholics were greatest in the prefrontal and temporal-parietal regions. Although both patient groups had abnormally larger cortical sulci and lateral and third ventricles than the controls, the alcoholics had significantly larger sulcal volumes in the frontal, anterior, and posterior parietal-occipital regions than the schizophrenics. This quantitative MRI study revealed different patterns of regional cortical volume abnormalities in schizophrenics and alcoholics. The schizophrenic group exhibited cortical gray matter volume deficits of modestly greater magnitude than that observed in the alcoholic group, and the alcoholics but not the schizophrenics exhibited cortical white matter volume deficits.